2017
DOI: 10.2196/mhealth.6654
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Patient-Centered mHealth App: A Tool for Adolescents With Type 1 Diabetes and Their Parents

Abstract: BackgroundType 1 diabetes (T1D) afflicts approximately 154,000 people under 20 years of age. Three-quarters of adolescents are not achieving glycosylated hemoglobin (HbA1c) targets, which leads to negative health outcomes. Mobile health (mHealth), the use of technology in health, has been used successfully to improve health in many chronic conditions, including diabetes.ObjectiveThe purpose of this study was to use patient-centered research methods to inform and improve the design and functionality of our T1D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 57 publications
3
78
0
Order By: Relevance
“…Other mHealth studies considered the usability and receptiveness of application-based tools using different forms of Likert scales [2,7] or qualitative measures from patient responses [5,6] to find important associations related to application quality and user opinions. These studies assessed a variety of health interventions and most had positive results when investigating topics such as usability [3] and acceptability [2,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mHealth studies considered the usability and receptiveness of application-based tools using different forms of Likert scales [2,7] or qualitative measures from patient responses [5,6] to find important associations related to application quality and user opinions. These studies assessed a variety of health interventions and most had positive results when investigating topics such as usability [3] and acceptability [2,7].…”
Section: Discussionmentioning
confidence: 99%
“…These mHealth interventions have been applied to monitoring postoperative care [2,3], diabetes self-management [4,5], smoking cessation [6,7], care and prevention of HIV and other sexually transmitted diseases [8], and more. As these interventions begin to spread throughout healthcare, there has been a growing interest in the response to these applications, including topics such as acceptability and feasibility [2], satisfaction by patients and providers [5], and efficiency [4]. However, there is limited research measuring users' comfort in operating smartphone functions, and whether comfort increases as a result of engagement with these applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, they only express opinions on potential use based on trying out the app with the assistance of a researcher. Such evaluations of technology prototypes through interviews are an important step in a user-centred design process and commonly reported in the health informatics literature, including in the area of diabetes (e.g., [23,[39][40][41][42]). The critical next step is a deployment study where patients and their carers can use and evaluate the app over several weeks or months in their daily lives to evaluate the actual impact on self-care.…”
Section: Limitationsmentioning
confidence: 99%
“…These studies support the use of digital solutions and demonstrate a promising next step in chronic disease management technology. In another case, Holtz et al [7] developed and tested a patient-centered mobile application using focus group interviews with teens having Type-1 Diabetes and their parents. Participants reported that they thought that the mobile application would help to improve communication among family members.…”
Section: Digital Solutions In Chronic Disease Managementmentioning
confidence: 99%
“…Researchers from Michigan State University proposed a mobile app, MyT1D Hero, to create a communication platform among teens with type-1 diabetes and their parents to support selfmanagement [7].…”
Section: Current Implementationsmentioning
confidence: 99%